SILENCE-A FABLE: GOTHIC AS WORLDVIEW - Ramis Rauf (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
This study aims to illuminate the gothic in the Romantic era through Edgar Allan Poe's A Fable. It seeks to answer the question: How does gothic express the worldview in Edgar Allan Poe's A Fable? This study employs the theory of genetic structuralism of Lucien Goldmann, who views literary works as a reflection of scholarly works, including their interrelationship with the social environment, which is the response of the collective subject (trans-individual subject). It occurs due to the shared taste and thought between authors as literary writers and readers in understanding literature as a human factor. The study's significant findings reveal that Gothic in Edgar Allan Poe's A Fable critiques the upheaval stemming from the Enlightenment era, leading to environmental degradation. It is depicted in prose narratives that mention a specific location, the Libyan region, which borders the Zaire River. The river is tainted by saffron. The title of this prose, Silence-A Fable, perfectly captures the silence of the environment, yet it also conveys a sense of restlessness, loneliness, solitude, mystery, tension, and horror. These features collectively embody the essence of the Gothic genre.